Strategi Komisi Penyiaran Indonesia Daerah Banten dalam Pengawasan Konten Televisi Lokal - Siti Nurul Aisyah; Achmad Nashrudin Priatna; Noerma Kurnia Fajarwati; Rizqi Fitrianti; Arfian Suryasuciramdhan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to examine the communication strategies implemented by the Regional Indonesian Broadcasting Commission (KPID) of Banten in educating and engaging the public in monitoring local television content. The research employed a qualitative approach with a descriptive study method. Data collection techniques included in-depth interviews with KPID Banten commissioners and community members, observation of socialization activities, and document analysis. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that KPID Banten applies educational and participatory communication strategies through the socialization of the Broadcasting Behavior Guidelines and Program Standards (P3SPS), publications on social media, and public discussion forums. The community actively contributes by reporting broadcast violations and participating in media literacy activities. However, challenges such as low media literacy and limited understanding of broadcasting regulations remain obstacles. This study recommends enhancing collaboration among KPID, local governments, and community groups to strengthen participatory-based broadcast monitoring.